The Specificities of Human Resource Management in Project Management - Jelena Ilić (European Project Management Journal, 2021)
Paper focuses on analysis of the human resource management in project management – from the perspective of the organisation and the individual. Firstly, paper will explore the theoretical perspective of the human resource management concept as it is applied to project-oriented organisations. Different approaches to project management will be reviewed (traditional and agile approach) and their implications to human resource management. Next, focus will be on the elements of human resource management such as competence development, career development, but also organisational culture and internal communication. Focus will also be on individuals – employees, on their competences and motivation as important factors of the successful achievement of the project goals. Questionnaire research will examine the way in which specific project environment impacts human resource management and motivation of employees in civil society organisations. Concluding remarks will provide theoretical conclusions and practical recommendations for the improvement of human resource management practices in project management.